Does the ballot reflect the voice of the labor force? an inquiry on the influence of unemployment on voter turnout - Agustin, Joshua Angelo Q.; Cruz, Franz Janssen S.; Mendoza, Nimfa (Quezon City School of Economics, University of the Philippines Diliman, 2021)
This paper analyzes the impact of unemployment on voter turnout in a developing country, specifically the Philippines. The aim is to show the relationship between the two in the Philippines due to the lack of studies present at the time of writing this paper. Using data procured from the Philippine Statistics Authority, Labor Force Survey, and the Family Income and Expenditure Survey, a panel dataset was formed which contains socioeconomic variables showing the economic situation of the seventeen regions in the 2010, 2013, 2016, and 2019 elections, along with socioeconomic factors that may affect the decision of registered voters to vote. To estimate the panel dataset, a fixed effects model was then used. Despite previous studies showing that there would be a higher turnout in the polls with more economic adversity in a developing country, the results of the study show otherwise. With a constant negative sign and the significance of the unemployment rate in the different fixed effects regression, the researchers conclude that there is a withdrawal effect in the Philippines - a result that could pose a question in the democracy of the country.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Unemployment -- Economic aspects -- Philippines; Political participation -- Economic aspects -- Philippines; Voter turnout -- Economic aspects -- Philippines